Nrf2 induces malignant transformation of hepatic progenitor cells by inducing β-catenin expression - Fragoulis, Athanassios; Schenkel, Julia; Schröder, Nicole; Brandt, Elisa Fabiana; Weiand, Mathias; Neu, Tabita; Ramadori, Pierluigi; Caspers, Tim; Kant, Sebastian; Pufe, Thomas; Mohs, Antje; Trautwein, Christian; et al. (Redox Biology, 2022)
The Nrf2 signaling pathway prevents cancer initiation, but genetic mutations that activate this pathway are found in various types of cancer. The molecular mechanisms underlying this Janus-headed character are still not understood. Here, we show that sustained Nrf2 activation induces proliferation and dedifferentiation of a Wnt-responsive perivenular hepatic progenitor cell population, transforming them into metastatic cancer cells. The neoplastic lesions display many histological features known from human hepatoblastoma. We describe an Nrf2-induced upregulation of β-catenin expression and its activation as the underlying mechanism for the observed malignant transformation. Thus, we have identified the Nrf2-β-catenin axis promoting proliferation of hepatic stem cells and triggering tumorigenesis. These findings support the concept that different functional levels of Nrf2 control both the protection against various toxins as well as liver regeneration by activating hepatic stem cells. Activation of the hepatic stem cell compartment confers the observation that unbridled Nrf2 activation may trigger tumorigenesis.
Gesehen am 18.01.2023